Effect of sustainability readiness on digital transformation adoption in SMEs - Citraresmi, Ardaneswari Dyah Pitaloka; Rucitra, Andan Linggar; Amalia, Faizatul; Mustaniroh, Siti Asmaul; Kartikaningrum, Widhistya (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2023)
SMEs face the problem of sustainability and readiness to implement digital transformation as part of the industrial revolution. Therefore, a process is needed to identify sustainability factors that can increase the readiness of SMEs to adopt digital change. This study aims to determine the influence of sustainability factors in the form of people, process, and technology that influence SMEs' readiness to adopt digital transformation. The research object is SMEs in various sectors with a literature study approach to develop a conceptual framework and data collection using a questionnaire. Construction testing and data analysis used statistical methods from confirmatory factor analysis, while the data testing process used the Partial Least Square (PLS) method. The results of the study show that toward international orientation (IO) and digital transformation readiness (DT), the sustainable people (SPe) and sustainable process (SPo) factors have a substantial direct influence. However, on the contrary, the sustainable technology factor (STe) has a weak direct impact. In comparison, the IO factor has a significant effect on DT. As a mediator of DT, IO has an invalid role in mediating SPe and STe but significantly mediates SPo. The results also show that an independent attribute of 71.4% influences DT. While IO has an independent attribute effect of 49.4%.